Housing and feeding strategies of goat farming in the Kilinochchi district - Kunarathinam, P.; Sinniah, J.; Thatchaneshkanth, S. (Eastern University, Sri Lanka, 2020)
A survey was carried out in four veterinary divisions of the Kilinochchi district viz. Karachchi, Kandawalai, Poonakary and Pachchilaippalli to study the feeding and housing strategies adopted by the goat farmers. A total of 291 farmers were interviewed with structured questionnaires to collect information on housing and feeding practices adopted by the goat farmers. Results showed, earthen housing (60.82%) was predominant in all four veterinary divisions while least farmers constructed elevated (wooden) housing (2.75%) for goats. Percentages of farmers allowing goats for grazing in the dry and rainy seasons were 80 and 20, respectively. Majority of the farmers adopted a grazing period of 4-8 hours and 1-4 hours in the dry and rainy season, respectively. Goats were either tied or untied in non-cropped lands or abandoned spaces during grazing. Less than 28% of the goat farmers grew fodder grass and fodder legumes. Average extend of fodder cultivation was around 0.16 acres except in Pachilaipalai veterinary division where the average extend was around 3 acres. Farmers reported that CO3 seems to be less palatable to goats. In the semi-intensive system of management goats were mainly fed with diverse plants and leaves, in addition kitchen wastes and human leftovers also was fed. Comparatively higher percentage of concentrates were given to lactating does and bucks than other stages of goats and the main concentrates fed were rice bran, coconut poonac, commercially available compound feed and gingelly poonac. It could be concluded that since farmers have been adopting the basic aspects of housing and feeding, they could be educated on appropriate housing and feeding strategies to improve the productive and reproductive efficiencies of goats in the Kilinochchi district.
Keywords: Dry zone; Feeding; Goat rearing; Grazing; Kilinochchi